As Ciências da Educação e a prática pedagógica: sentidos atribuídos por estudantes do curso de Pedagogia - Nunes, Claudio Pinto (2010)
This study focuses on the initial formation of the pedagogue in college, especially the formation that takes place in the Pedagogy Course. It is bound by the following question: what senses are attributed by the Pedagogy Trainees regarding the relation between the Education Science knowledge and the Pedagogic Practice knowledge developed in the Pedagogy Course of UESB, in order to build up teaching knowledge and practice? Therefore it aims to reflect on the relations between the Education Science framework and the Pedagogic Practice under the supervised classes that belong to the Pedagogy Course. It presents the implications and contextualizations concerning the pedagogue formation as a historic and cultural process, emphasizing the current moment of this formation. It is based on the idea that the senses trainees, future pedagogues, attribute to their own formation process reflect on the learning of theorical and practical knowledge that validates the process of teachers formation, especially the pedagogue formation. Accordingly, it believes that the senses attributed by the students of teachers initial formation courses regarding the Education Science knowledge and Pedagogic Practice knowledge are essential as organizers in the construction of teaching knowledge and practice while the supervised classes take place. The theorical and methodological option is based on the studies of Qualitative Epistemology by Gonzalez Rey. Empiric studies took place at the Pedagogy Course of Universidade Estadual do Sudoeste da Bahia (UESB), located in the city of Vitória da Conquista/Bahia. The students who took part in this research were six graduating ones, enrolled in the last two semesters of the referred course, stage when the supervised classes happen. The procedures used in the organization of collected information consist of analysis of documents such as the mentioned course curricular project and the students reports, besides interactive and provocative talks to the students. The results show the senses students attribute to Educational Science theorical basis to practice to Pedagogic Practice opportunity of feeling as if they were teachers and to the relation between Education Science and Pedagogic Practice opportunity of experiencing the relation between theory and practice. Besides, the theorizations students have about the relation between theory and practice in teachers formation are also presented. Consequently, it is emphasized that the supervised classes are the moments in which the trainees might understand the relations between thought and pedagogic practice, building the senses attributed to the relation between the Education Science knowledge and the ones of Pedagogic Practice as organizers in the teaching knowledge and practice. In this context, the trainees build some knowledge regarding what it means to be a teacher, which is not written or published, due to its subjective dimension, but circumscribed in their pedagogic practice while the supervised classes take place and when professional teaching practice becomes effective